2013
DOI: 10.1590/1516-3180.2013.1313470
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among Iranian patients with beta-thalassemia major using the SF-36 questionnaire

Abstract: CONTEXT AND OBJECTIVE: Patients with beta-thalassemia major (β-TM) experience physical, psychological and social problems that lead to decreased quality of life (QoL). The aim here was to measure health-related QoL and its determinants among patients with β-TM, using the Short Form-36 (SF-36) questionnaire. DESIGN AND SETTING: Cross-sectional study at the Hematology Research Center of Shiraz University of Medical Sciences, in southern Iran. METHODS: One hundred and one patients with β-TM were randomly selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
33
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 29 publications
3
33
1
1
Order By: Relevance
“…The patients in our study had lower RE function compared to other dimensions. This is consistent with the results of Safizadeh et al 19 and Khani et al 8 Moreover, the mean of physical and mental dimensions in the present study were similar to those reported by Mantovani et al, 11 but lower than those reported by Haghpanah et al 18 In addition, we found that the patients' functionality in almost all the dimensions decreased with age. With increasing age as well as physical problems and functional limitation, patients encounter other problems such as extending family size, continuing education, and finding a good job, which will result in various psychological problems.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The patients in our study had lower RE function compared to other dimensions. This is consistent with the results of Safizadeh et al 19 and Khani et al 8 Moreover, the mean of physical and mental dimensions in the present study were similar to those reported by Mantovani et al, 11 but lower than those reported by Haghpanah et al 18 In addition, we found that the patients' functionality in almost all the dimensions decreased with age. With increasing age as well as physical problems and functional limitation, patients encounter other problems such as extending family size, continuing education, and finding a good job, which will result in various psychological problems.…”
Section: Discussionsupporting
confidence: 93%
“…8,16 The mean of this dimension in Safizadeh et al 19 was similar to our study, but RE was not the weakest dimension in their study. Contrary to these, the best function of RE were seen in Baraz Pordanjani's study, 17 and Haghpanah et al 18 showed that it has the greatest effect after physical functioning. The patients in our study had lower RE function compared to other dimensions.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations